Rethinking training and active labour policies in Italy: exercises in resilience in times of COVID-19 - Biancolini, Alessandra [Verfasser]; Simoncini, Andrea [Verfasser] (My University, 2022)
„The pandemic represents at the same time a difficult crisis in the global economies and a challenge to innovate policies devoted to education and Vocational Training. The advent of distance learning and agile working, born in the first emergency period and rapidly accepted as solutions at hand, concretely boosted the development of digitisation in all the sectors, while the stop to mobility revamped the debate around the need for greener economies and protected environment. Despite of that, the current crisis in the short and medium terms represents a loss of competitiveness, from labour to education, if policies do not use the opportunity to reskill and upskill the parts of population at risk of social exclusion and if the school system does not integrate skills anticipation methods. To face this situation, Italy is exercising the resilience through a systemic approach outlined in the National Plan for Recovery and Resilience that is declining the Next Generation EU at the national level. In the next five years, investments are provided to revamp active labour policies and reshape lifelong learning policies with a focus on upskilling and reskilling in digital and green economy. Vocational Education and Training will be also supported through dedicated funding with the aim of consolidating the very positive trends noticed in dual education systems since their formal birth in 2015.“ (authors’ abstract; BIBB-Doku)
Keywords: S 2.3 Berufsbildungspolitik; I 2.2.1 Westeuropa; 370; Berufsbildung; Pandemie; Auswirkung; Digitalisierung; Bildungspolitik; Duales System; Qualifizierung; Lebenslanges Lernen; Italien